Pemanfaatan dan Prospek Pelepah Batang Pisang Kepok sebagai Bahan Baku Mebel - Fauziati Fauziati (Balai Riset dan Standardisasi Industri Samarinda, 2016)
The research results have shown that the products made by the machine have relatively smaller of the coefficient of variance (cv) than the products made by the crafters.The cv of the thickness is a variation of data in the process of thickness measurement. The thickness cv of the sample made by the machine is 3. 7 % ;1,6 % ;and 5,8 % for the sample taken the outer layer of the stem (G1) from the middle layer of the stem (G2) and from the inner layer of the stem (G3) respectively .In addition, the thickness increase the variation of data goes up . It shows that the thickness is not even and the decrease of tensile strength of G4 is 791.7 N/89.7 kg; G1 is 465.3 testing of aIl treatments (G1,G2 .G3 and G4) is good (3- 4).